Small Open Reading Frames, How to Find Them and Determine Their Function - Kute, Preeti Madhav; Soukarieh, Omar; Tjeldnes, Håkon; Trégouët, David-Alexandre; Valen, Eivind (Frontiers in Genetics, 2022)
Recent advances in genomics and molecular biology have revealed an abundance of small open reading frames (sORFs) across all kinds of transcripts. While these sORFs are often assumed to be non-functional, many have been implicated in physiological functions and a significant number of sORF-altering variants have been described in human diseases. Thus, sORFs may represent a hidden repository of functional elements that could serve as therapeutic targets. Unlike protein-coding genes, it is not necessarily the encoded peptide of an sORF that enacts its function, sometimes simply the act of translating an sORF might have a regulatory role. Indeed, the most studied sORFs are located in the 5’UTRs of coding transcripts and can have a regulatory impact on the translation of the downstream protein-coding sequence. However, sORFs have also been abundantly identified in non-coding RNAs including lncRNAs, circular RNAs and ribosomal RNAs suggesting that sORFs may be diverse in function. Of the many different experimental methods used to discover sORFs, the most commonly used are ribosome profiling and mass spectrometry. These can confirm interactions between transcripts and ribosomes and the production of a peptide, respectively. Extensions to ribosome profiling, that also captures scanning ribosomes, have further made it possible to see how the sORFs impacts translation initiation of mRNAs. While high-throughput techniques have made the identification of sORFs less difficult, defining their function, if any, is typically more challenging. Together, the abundance and potential function of many of these sORFs argues for the necessity of including sORFs in gene annotations and systematically characterizing these to understand their potential functional roles. In this review, we will focus on the high-throughput methods used in the detection and characterization of sORFs.